IMPLEMENTASI APLIKASI QUIZIZZ TERHADAP MOTIVASI BELAJAR PENDIDIKAN PANCASILA SISWA KELAS VIII MTS NEGERI I MALUKU TENGAH - Ely, Lingga Nur Syahbany; Abas, Aisa; Gaite, Titus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to examine the level of students' learning motivation in response to the use of the Quizizz application in the Pancasila Education subject for grade VIII students at MTs Negeri 1 Maluku Tengah. The research utilizes a pre-experimental approach with a One-Group Pretest-Posttest Design. The independent variable is the Quizizz application, while the dependent variable is the learning motivation in Pancasila Education. The population includes 8 classes, with a total of 235 students. Sampling was conducted through Random Sampling, resulting in a sample of one class (VIII.a) consisting of 30 students. Research data were obtained by administering pre-tests and post-tests. The findings reveal a significant increase in students' learning motivation following the use of the application, evidenced by an increase in the motivation score percentage from 66,48% (Agree/Good/Favorable) in the pre-test to 89,18% (Strongly Agree/Very Good/Highly Favorable) in the post-test. Hypothesis testing indicated a significance level of < 0.05, with 0.000 < 0.05, leading to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (H1). Based on these results, it can be concluded that the application of Quizizz positively influences students' motivation to learn Pancasila Education in grade VIII at MTs Negeri 1 Maluku Tengah.